2021
DOI: 10.1111/fwb.13824
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the microbial community structure and functional diversity of a dam‐regulated river undergoing gravel bar restoration

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 102 publications
2
4
0
Order By: Relevance
“…This finding implies that the taxonomic structure divergence observed between points or gravel bars reflects different putative metabolic functions that emerged among the heterogeneous environments. This result is in good agreement with previous studies on stream microbial communities (Serrana et al, 2022;Galand et al, 2018;Fasching et al,2020). However, it should be noted that the use of 16S rRNA gene sequences to predict metabolic function is constrained by the limited information content of the amplicon and limited databases.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding implies that the taxonomic structure divergence observed between points or gravel bars reflects different putative metabolic functions that emerged among the heterogeneous environments. This result is in good agreement with previous studies on stream microbial communities (Serrana et al, 2022;Galand et al, 2018;Fasching et al,2020). However, it should be noted that the use of 16S rRNA gene sequences to predict metabolic function is constrained by the limited information content of the amplicon and limited databases.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies on freshwater microbial communities also estimated functional traits based on taxonomic annotation using databases (e.g. SILVA rRNA, Greengenes, National Center for Biotechnology, and Ribosomal Database Project) and 16S rRNA metabarcoding (Serrana et al, 2022;Galand et al, 2018;Fasching et al, 2020) Several studies have demonstrated the validity and utility of this approach, although the estimated functional traits were putative as 16S rRNA metabarcoding could not identify functional genes in the genome, and database limitations allowed annotating only a proportion of the taxa. However, applied cases are still scarce and further verifications would be required.…”
Section: Introductionmentioning
confidence: 99%
“…The sediment samples assessed in this study were collected from three sites (i.e., sites A and C are from up-welling zones; site B from a down-welling zone) on selected gravel bars in the Trinity River assessed in the study of Serrana et al [ 38 ]. The experimental procedure of the sediment-associated microbial community profiling employed in this study is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sediment samples from three sites (i.e., sites A and C are from up-welling zones; site B from a down-welling zone) were collected approximately 10 cm below the submerged surface of selected gravel bars in the Trinity River assessed in the study of Serrana et al [ 38 ]. The Trinity River is a large gravel-bed river impounded by the Trinity Dam (164 m a.b.l.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding the functional traits of each species could contribute to deepening our knowledge of the biological processes and ecological mechanisms that shape community structure variation along environmental gradients. Recent studies on freshwater microbial communities also estimated functional traits based on taxonomic annotation using databases (e.g., SILVA rRNA, Greengenes, National Center for Biotechnology, and Ribosomal Database Project) and 16S rRNA gene sequencing (Galand et al, 2018;Fasching et al, 2020;Serrana et al, 2022). Several studies have demonstrated the validity and utility of this approach, although the estimated functional traits were putative as 16S rRNA gene sequencing could not identify functional genes in the genome, and database limitations allowed annotating only a proportion of the taxa.…”
Section: Introductionmentioning
confidence: 99%